Suppressive role of E3 ubiquitin ligase FBW7 in type I diabetes in non-obese diabetic mice through mediation of ubiquitination of EZH2 - Yingxue Guo (Nature Publishing Group, 2021)
Abstract The current study tried to uncover the molecular mechanism of E3 ubiquitin ligase F-box and WD repeat domain-containing 7 (FBW7) in a heritable autoimmune disease, type I diabetes (T1D). After streptozotocin-induced T1D model establishment in non-obese diabetic (NOD) mouse, the protein expression of FBW7, enhancer of zeste homolog 2 (EZH2), and Zinc finger and BTB domain containing 16 (ZBTB16) was quantified. Next, splenocytes and pancreatic beta cells were isolated to measure the production of pro-inflammatory cytokines in splenocytes, as well as islet beta-cell apoptosis. Additionally, the stability of EZH2 induced by FBW7 was analyzed by cycloheximide chase assay. The binding affinity of FBW7 and EZH2 and the consequence of ubiquitination were monitored by co-immunoprecipitation assay. Last, a chromatin immunoprecipitation assay was employed to analyze the accumulation of EZH2 and H3K27me3 at the ZBTB16 promoter region. Our study demonstrated downregulated FBW7 and ZBTB16 and upregulated EZH2 in diabetic NOD mice. Overexpression of FBW7 in the NOD mice inhibited pro-inflammatory cytokine release in the splenocytes and the apoptosis of islets beta cells. FBW7 destabilized EZH2 and accelerated ubiquitin-dependent degradation. EZH2 and H3K27me3 downregulated the ZBTB16 expression by accumulating in the ZBTB16 promoter and methylation. FBW7 upregulates the expression of ZBTB16 by targeting histone methyltransferase EZH2 thus reducing the occurrence of T1D.